2020
DOI: 10.22201/enesl.20078064e.2020.22.76243
|View full text |Cite
|
Sign up to set email alerts
|

Pensiones contributivas como fuente de ingresos en la vejez prevista por los jóvenes mexicanos

Abstract: <p><strong>Objetivo:</strong> analizar el impacto que tienen algunas variables sociodemográficas y el conocimiento financiero en la probabilidad de que los jóvenes mexicanos esperen financiar su vejez con pensiones contributivas.</p><p><strong>Diseño metodológico:</strong> se empleó la información obtenida en la Encuesta Nacional de Inclusión Financiera de 2018 correspondiente a los jóvenes de entre 18 y 29 años de edad, así como una regresión logística binaria.</p&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Results also show that gender plays a fundamental role in retirement planning. Atlatenco et al (2020) analyzed factors that influenced the probability that young Mexicans (18-29 years old) would resort to contributory pensions when older. They found that gender, marital status, town size, region, level of studies, and work income are significant variables.…”
Section: Mexicans´ Financial Literacymentioning
confidence: 99%
“…Results also show that gender plays a fundamental role in retirement planning. Atlatenco et al (2020) analyzed factors that influenced the probability that young Mexicans (18-29 years old) would resort to contributory pensions when older. They found that gender, marital status, town size, region, level of studies, and work income are significant variables.…”
Section: Mexicans´ Financial Literacymentioning
confidence: 99%